Interaction of bentonite with dodecyl-benzyl-dimethylammonium bromide and N-[1-(ethoxycarbonyl)pentadecyl] trimethylammonium bromide - Kalousová, Jaroslava (Univerzita Pardubice, 1999)
Interaction of bentonites with tetrasubstituted ammonium cations of surface-active compounds were studied both by classic heating and in microwave field. The intercalation of the layered silicate which is contained in the bentonite proceeds as an ion exchange, and the interlayer distance increases during this process. Products of the reactions were characterized by gravimetry, DTA, DTG, IR, and X-ray diffraction.
Keywords: bentonity; vrstevnaté materiály; interkaláty; reakce bentonitů; iontová výměna; spektra